Frequent homozygous deletion of the LKB1/STK11 gene in non-small cell lung cancer - Gill, RK (2011)
LKB1/STK11 is a tumor suppressor and a negative regulator of mammalian target of rapamycin signaling. It is inactivated in 30% of lung cancer cell lines but only 5–15% of primary lung adenocarcinomas. There is evidence that homozygous deletion (HD) of chromosome 19p at the LKB locus contributes to the inactivation of the gene in primary human lung cancers. Here, we used several complementary genetic approaches to assess the LKB1 locus in primary non-small cell lung cancers (NSCLCs). We first analyzed 124 NSCLC cases for allelic imbalance using eight microsatellite markers on chromosome 19p, which revealed an overall rate of 65% (80 of 124) loss of heterozygosity (LOH). We next used chromogenic in situ hybridization (CISH) to directly examine the chromosomal status of the LKB1 locus. In all, 65 of 124 LOH tested samples were available for CISH and 58 of those (89%) showed either loss of one copy of chromosome 19p (LOH, 40 of 65 cases, 62%) or both copies (HD 18 of 65 cases, 28%). The occurrence of HD was significantly more frequent in Caucasian (35%) than in African-American patients (6%) (P=0.04). A total of 62 of 124 samples with LOH at one or both markers immediately flanking the LKB1 gene were further analyzed by directly sequencing the complete coding region, which identified 7 of 62 (11%) tumors with somatic mutations in the gene. Jointly, our data identified total inactivation of the LKB1 gene by either HD or LOH with somatic mutation in 39% of tested samples, whereas loss of chromosome 19p region by HD or LOH at the LKB1 region occured in 90% of NSCLC.